2001
DOI: 10.1029/2001jb000433
|View full text |Cite
|
Sign up to set email alerts
|

Erosion and rheology controls on synrift and postrift evolution: Verifying old and new ideas using a fully coupled numerical model

Abstract: Abstract. We use a fully coupled asymmetric dynamic finite element model to study interactions between thermomechanical behavior and surface processes during continental rift evolution. The model accounts for (1) nonlinear brittle-elastic-ductile rheology, layered lithological structure, and faulting; (2) heat transport and thermal buoyancy forces; and (3) "true" erosion and sedimentation (grid elements are eliminated and recreated). Faults are not predefined but are self-localized; their distributions and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(176 citation statements)
references
References 54 publications
7
167
1
1
Order By: Relevance
“…As discussed by Burov and Diament (1995) and Burov and Poliakov (2001) Similar conclusions were derived from a study by Huismans and Beaumont (2011). In their study, they were able to reproduce a margin setting as typically observed in the south Atlantic by means of a model in which the upper and lower lithosphere are decoupled during extension due to asthenospheric inflow.…”
Section: Implications For Additional Subsidence Componentssupporting
confidence: 69%
“…As discussed by Burov and Diament (1995) and Burov and Poliakov (2001) Similar conclusions were derived from a study by Huismans and Beaumont (2011). In their study, they were able to reproduce a margin setting as typically observed in the south Atlantic by means of a model in which the upper and lower lithosphere are decoupled during extension due to asthenospheric inflow.…”
Section: Implications For Additional Subsidence Componentssupporting
confidence: 69%
“…The numerical studies mentioned above investigated fundamental mechanical folding and necking processes, but numerical solutions are also useful to study the coupling of folding and necking with other processes such as (i) the generation of heat during folding due to dissipative rock deformation (shear heating) and the related thermal softening caused by thermo-mechanical feed-back with temperaturedependent rock viscosity (Hobbs et al, 2007(Hobbs et al, , 2008Burg and Schmalholz, 2008), (ii) the conversion of macroscale mechanical work into microscale mechanical work during the reduction and growth of mineral grain size and related softening due to grain size reduction (Peters et al, 2015), (iii) the impact of metamorphic reactions on rock deformation (Hobbs et al, 2010), (iv) coupling of crustal folding or necking with erosion in 2-D (Burg and Podladchikov, 2000;Burov and Poliakov, 2001) and 3-D (Collignon et al, 2015) or (v) the coupling of folding with salt diapirism (Fernandez and Kaus, 2014). A detailed outline of a coupled thermodynamic approach to study rock deformation and the resulting structures is given in the recent textbook by Hobbs and Ord (2014).…”
Section: Numerical Simulations and Coupled Modelsmentioning
confidence: 99%
“…Over the last ~15 y, important insights have derived from numerical models (e.g., Burov and Poliakov, 2001;Lavier and Buck, 2002;Lavier and Manatschal, 2006;Beaumont, 2007, 2011) and from observations at mature, magma-poor passive margins (Boillot et al, 1987;Reston et al, 1995;Manatschal et al, 2001;Whitmarsh et al, 2001;Osmundsen and Ebbing, 2008) where activity has ceased, but early synrift stratigraphy is often difficult to image and sample due to deep burial and tectonic overprinting. Instead, this project will study the young, seismically active Corinth rift with a unique existing data set to resolve, at high temporal and spatial resolution, how faults initiate and link, how strain is distributed over time, and how the landscape responds during the first few million years of continental rifting.…”
Section: Introductionmentioning
confidence: 99%